Artificial reefs and their effects on fish assemblages in a Brazilian reservoir and Tailrace - Freitas, Carlos E.C.; Petrere Jr, Miguel [UNESP]; Abuabara, Maria A.P. [UNESP] (My University, 2002)
In this paper, we evaluate the effects of artificial reefs on fish assemblages in a hypereutrophic reservoir and in the lotic zone immediately below dam. Fish diversity was highest in the lotic zone relative to the reservoir. We also found an inverse relationship between diversity and distance from the river margin. Catches near the artificial reefs were more diverse than in control areas. A seasonal effect, possibly caused by variation in temperature, was significant in all comparisons. We argue that, in a scale of local effects, the ecological function of these structures would be similar to refuges.
Keywords: Artificial reefs; Diversity; Fish; Lotic zone; Refuges; artificial reef; dam; eutrophic environment; ichthyofauna; lotic environment; refuge; restoration ecology; species diversity; Brazil; Ichthyofauna